Comparative efficiency of TiO2 nanoparticles in suspension vs. immobilization into P(VDF–TrFE) porous membranes. Issue 15 (1st February 2016) - Martins, P. M.; Miranda, R.; Marques, J.; Tavares, Carlos. J.; Botelho, G.; Lanceros-Mendez, S.
Abstract : Optimized photocatalytic membranes based on TiO2 and NaY immobilized into P(VDF–TrFE) have been developed showing a degradation efficiency of 96%. Abstract : Photocatalytic processes based on titanium dioxide (TiO2 ) nanoparticles have attracted increasing attention in the last decades. However, approaches based on nanoparticles show some drawbacks, in particular due to the need for expensive and time consuming post-treatment of nanoparticles filtration/separation. This hindrance demands the development of immobilized configurations with tailored properties, as an alternative to allow simple recovery of the photocatalytic particles. Thus, this work reports on the development of photocatalytic membranes based on TiO2 nanoparticles immobilized into a poly(vinylidenefluoride–trifluoroethylene) (P(VDF–TrFE)) membrane and the comparative study of their performance with dispersed TiO2 nanoparticles. Photocatalytic nanocomposite membranes with a highly porous structure (∼75%) and controlled wettability by NaY addition were successfully produced. These properties were paramount to achieve a methylene blue degradation efficiency of 96% in 40 min under ultraviolet (UV) irradiation, corresponding to an efficiency loss of just 3% regarding the TiO2 nanoparticle assays.